2013
DOI: 10.2215/cjn.01430213
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Socioeconomic Disparities in the Allocation of Expanded Criteria Donor Kidneys

Abstract: SummaryBackground and objectives In carefully selected individuals, receiving expanded criteria donor (ECD) kidneys confer a survival advantage over remaining on dialysis. However, wait lists for ECD kidneys often include a significant proportion of young patients, who have no predictable survival benefit from ECD kidneys. This study hypothesized that educational and socioeconomic factors might influence a younger patient's decision to accept an ECD kidney.Design, setting, participants, & measurements This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Although several studies show significant impact of socioeconomic variables on WTD , there is lack of consensus on the sign of influence. Evidence from Switzerland shows education as a significant predictor of organ donation, but others show no such link . Another study on Canada found a positive link between income and WTD .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although several studies show significant impact of socioeconomic variables on WTD , there is lack of consensus on the sign of influence. Evidence from Switzerland shows education as a significant predictor of organ donation, but others show no such link . Another study on Canada found a positive link between income and WTD .…”
Section: Literature Reviewmentioning
confidence: 99%
“…We were able to identify only one study that demonstrated a very strong association between poor health literacy and lack of patients’ enrollment on kidney transplant lists [ 40 ]. It is possible that health literacy may explain part of the currently described disparity in surgical services [ 53 , 54 ]. Future studies attempting to explain disparities in surgical care should incorporate measurements of health literacy in their evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…HLA is one potential driver of racial/ethnic disparities in transplant 33 , leading to gaps in the rate of transplants between whites and racial/ethnic minorities, despite greater willingness by minorities to accept poorer quality (i.e. expanded criteria donor) organs 34 .…”
Section: Discussionmentioning
confidence: 99%